Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Pendidikan - Taufiq, Shodiq; Abdullah, Abdullah (Civiliza Publishing, Indonesia., 2023)
The aim of this research is to understand and analyze the planning, implementation and evaluation of human resource management in improving the quality of education at MI Nahdlatul Ulama Kraksaan and SD Muhammadiyah Creative Kraksaan. The research method uses a qualitative approach with a multisite study type of research. The data collection techniques used were participant observation, in-depth interviews and documentation. Data analysis techniques use individual data analysis and cross-site analysis. Checking the validity of data with credibility, transferability, dependability and confirmability. The results of this work are a) Good and sustainable human resource planning is the key to improving the quality of education in schools. b) Recruitment of human resources based on clear criteria and a transparent process is a key step in ensuring quality human resources to improve the quality of education. c) Continuous training and development of human resources, both through external and internal programs, is an important effort to ensure that schools have quality human resources in order to improve the quality of education.